Let the per-minute rental fee be denoted as \( x \).
For Ross's first rental:
- The time he used the bike is 64 minutes.
- He received a $10 new-customer discount.
Thus, the cost for the first rental can be expressed as: \[ \text{Cost}_1 = 64x - 10 \]
For Ross's second rental:
- The time he used the bike is 39 minutes.
The cost for the second rental is: \[ \text{Cost}_2 = 39x \]
Given that Ross was charged the same amount for both rentals, we set the costs equal: \[ 64x - 10 = 39x \]
To solve for \( x \), we first rearrange the equation: \[ 64x - 39x = 10 \] \[ 25x = 10 \] Now divide both sides by 25: \[ x = \frac{10}{25} = \frac{2}{5} = 0.4 \]
Therefore, the per-minute fee to rent an electric bike is: \[ \boxed{0.4} \]
To verify, we can calculate both costs using \( x = 0.4 \).
For the first rental: \[ \text{Cost}_1 = 64(0.4) - 10 = 25.6 - 10 = 15.6 \]
For the second rental: \[ \text{Cost}_2 = 39(0.4) = 15.6 \]
Both costs are equal, confirming that the per-minute fee is indeed: \[ \boxed{0.4} \]